CORRECTION OF CHANGES OF THE ORAL CAVITY'S MICROFLORA DEPENDS UPON THE DURATION OF REMOVABLE DENTURES USE - T. Y. Divnych (Ukrainian Medical Stomatological Academy, 2015)
At the present stage of Prosthetic Dentistry treat defects of teeth and dentition, accompanied by the introduction of the mouth dentures a foreign body should be considered taking into account the combined effect on the entire dentition system as prosthesis provides not only preventive, therapeutic, but side effects the surrounding tissues and organs of the mouth, and contributes to the development of pathogenic organisms. Clinicians makes aggressiveness microbial environment of the oral cavity and constantly seek to improve the ways and means of reducing. To date, the actual problem is a full and adequate antimicrobial therapy including scientific sound strategy and tactics in the application of antimicrobial agents. Correction microbiological violations is an indispensable element in the treatment of diseases of the oral mucosa. And despite the negative aspects of the impact of partial dentures on tissue prosthetic bed still need to look for ways to eliminate their influence, so now a way of actual pharmacological therapy of oral microflora in patients with partial dentures is normalized. In particular, such issues as drug correction of microflora of the oral cavity in patients with different terms of use of partial dentures previously studied, so we will hope on the best result. The aim was to develop a method of medical correction changes the microflora of the oral cavity in patients with partial dentures. In Clinic of Prosthetic Dentistry examination of the patients was conducted by the conventional method, including complaints of patients, life history, case history, evaluated data locally and external examination of the oral cavity using a standard set of dental tools. For the purpose of choosing the best medications to correct microflora of the oral cavity of patients with partial dentures we prescribed the patients such drugs as ,,Kofol" and ,,Trahisan". To assess the microbial balance of the oral cavity of patients under the influence of the use of treatment, the study of qualitative and quantitative composition of the microflora was performed at National 1sm2 surface of the prosthesis, which was harvested material. Using bacteriological method selected colonies carried the identification of aerobic and facultative anaerobic bacteria. In our research work we drew attention to the rate of growth of colonies of each type of sectors cups sown according to the method of Gold , it is possible to determine the concentration of bacteria of each species. The patients with partial dentures in most cases have problems with miсrobioсenosis of oral cavity. For effective pharmacological therapy in patients with partial dentures we prescribed such medicines as ,,Kofol" and ,,Trahisan". The results of microbiological studies have shown that ,,Kofol" didn't influence on the microflora of the oral cavity, while the drug ,,Trahisan" helps to recover the resident microflora of the mouth and inhibits transient microflora with high virulence.